Análisis del impacto de la digitalización en la eficiencia de los procesos aduaneros en puertos - Rodriguez Plata, Lisandra (Machala : Universidad Técnica de Machala, 2025)
This research addresses how digital transformation has optimized customs management in one of the most important ports in Ecuador. It is highlighted that digitalization is a key factor to improve operational efficiency, reduce costs and waiting times, and mitigate problems such as port congestion and excessive bureaucracy. The study is justified by the need to modernize customs processes in Puerto Bolívar, where the lack of adequate technological infrastructure limits competitiveness and affects foreign trade. The objectives of the research are: to evaluate the impact of digitalization on the reduction of waiting times and productivity, to propose measures to reduce dependence on manual processes, and to analyze how the lack of technology affects the implementation of digital solutions. In the development, the evolution of digitalization in the global and local context is explored, highlighting tools such as the ECUAPASS system, which has allowed the electronic transmission of customs declarations, reducing clearance times by 30% and minimizing errors. It also discusses international examples of ports that have implemented digital technologies, such as Rotterdam, Singapore, and Los Angeles, where automation and the use of artificial intelligence have improved operational efficiency. However, in Puerto Bolívar, challenges persist, such as the presentation of physical documents, manual reviews of returns, and the lack of integration between actors, which slows down total optimization. The methodology used is qualitative, with a non-experimental and cross-sectional approach, based on documentary review and interviews with customs officials, clearance agents and exporters. The results reveal that although digitalization has reduced clearance times from 7-10 days to 3-5 days and increased productivity, there are still manual processes that limit efficiency, such as cash payment management and physical inspections of goods. In addition, it is identified that the lack of adequate technological infrastructure and poor interoperability between systems are significant barriers. In the conclusions, it is emphasized that digitalization has positively transformed cargo management and the accuracy of procedures, but it is necessary to invest in technology, train staff and promote collaboration between the public and private sectors to overcome current limitations. The study recommends deepening the use of emerging technologies, such as artificial intelligence and blockchain, and developing an action plan that prioritizes the modernization of technological infrastructure. This would not only optimize customs processes in Puerto Bolívar, but also contribute to the economic growth and competitiveness of Ecuador's foreign trade.
La presente investigación aborda cómo la transformación digital ha optimizado la gestión aduanera en uno de los puertos más importantes de Ecuador. Se destaca que la digitalización es un factor clave para mejorar la eficiencia operativa, reducir costos y tiempos de espera, y mitigar problemas como la congestión portuaria y la burocracia excesiva. El estudio se justifica por la necesidad de modernizar los procesos aduaneros en Puerto Bolívar, donde la falta de infraestructura tecnológica adecuada limita la competitividad y afecta el comercio exterior. Los objetivos de la investigación son: evaluar el impacto de la digitalización en la reducción de tiempos de espera y la productividad, proponer medidas para disminuir la dependencia de procesos manuales, y analizar cómo la carencia de tecnología afecta la implementación de soluciones digitales. En el desarrollo, se explora la evolución de la digitalización en el contexto global y local, destacando herramientas como el sistema ECUAPASS, que ha permitido la transmisión electrónica de declaraciones aduaneras, reduciendo tiempos de despacho en un 30% y minimizando errores. También se analizan ejemplos internacionales de puertos que han implementado tecnologías digitales, como Róterdam, Singapur y Los Ángeles, donde la automatización y el uso de inteligencia artificial han mejorado la eficiencia operativa. Sin embargo, en Puerto Bolívar persisten desafíos, como la presentación de documentos físicos, revisiones manuales de declaraciones, y la falta de integración entre actores, lo que frena una optimización total. La metodología empleada es cualitativa, con un enfoque no experimental y transversal, basado en revisión documental y entrevistas a funcionarios de aduanas, agentes de despacho y exportadores. Los resultados revelan que, aunque la digitalización ha reducido los tiempos de despacho de 7-10 días a 3-5 días y aumentado la productividad, aún existen procesos manuales que limitan la eficiencia, como la gestión de pagos en efectivo y las inspecciones físicas de mercancías. Además, se identifica que la falta de infraestructura tecnológica adecuada y la escasa interoperabilidad entre sistemas son barreras significativas. En las conclusiones, se enfatiza que la digitalización ha transformado positivamente la gestión de cargas y la precisión de los trámites, pero se requiere invertir en tecnología, capacitar al personal y fomentar la colaboración entre el sector público y privado para superar las limitaciones actuales. El estudio recomienda profundizar en el uso de tecnologías emergentes, como inteligencia artificial y blockchain, y desarrollar un plan de acción que priorice la modernización de la infraestructura tecnológica. Esto no solo optimizaría los procesos aduaneros en Puerto Bolívar, sino que también contribuiría al crecimiento económico y la competitividad del comercio exterior de Ecuador.
Keywords: DIGITALIZACIÓN; PROCESOS ADUANEROS; EFICIENCIA OPERATIVA; TECNOLOGÍAS EMERGENTES